2014
DOI: 10.5513/jcea01/15.3.1497
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structure of the regional agricultural production (South Bohemian region)

Abstract: The organic farming shows growth trend all over the world. It became an integral part of the agricultural production not only in the developed countries, but also in the so called Third World countries. In the latter countries, the organic farming develops mainly in connection with the fair trade projects. The share of the organic farming in the agricultural land is in many countries above 10%, including the Central and Eastern European countries. The Czech Republic actively supports the organic production. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Together with the sectors of biofuels (2 925 jobs) and biogas (1 000 jobs) we can see that bioenergy is now employing more than two thirds of all RE related workers. These jobs are primarily concentrated to rural areas, which is beneficial for their economic and social stabilization [57], [58], [59] and [60].…”
Section: Data Sourced From: the State Of Renewable Energies In Europementioning
confidence: 99%
“…Together with the sectors of biofuels (2 925 jobs) and biogas (1 000 jobs) we can see that bioenergy is now employing more than two thirds of all RE related workers. These jobs are primarily concentrated to rural areas, which is beneficial for their economic and social stabilization [57], [58], [59] and [60].…”
Section: Data Sourced From: the State Of Renewable Energies In Europementioning
confidence: 99%
“…On the other hand, part of the organic crops and products is sold for conventional prices and processed with conventional food processors. For instance Doležalová et al (2014) concluded the organic production in Czech Republic constantly increases (and concretely in the South Bohemia as well) and one of tasks of researchers should be the topic of organic food processing and marketing in order to simplify the organic food marketing and to increase the sales of organic food as well. The question of organic food marketing is and will be certainly a subject of discussion on short supply chains with organic food (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…AD plants have become a significant alternative income for farmers in times when their revenues from traditional agricultural activities are declining. Despite original policy ambitions, it is less clear to what extent AD plants have been an effective tool for limiting the impacts of climate change or for local development support (Doležalová et al, 2009, 2014a, 2014b, Ženka et al, 2016or Duzi et al, 2017. It is therefore important to research also the attitudes and views of farmers on this significant change in the use of agricultural land Prousek 2016, Silva andDelicado, 2017).…”
Section: Introductionmentioning
confidence: 99%